Composition of the essential oil of Cistus laurifolius L. from Turkey - (:unkn) unknown (ALLURED PUBL CORP, 2004)
The water distilled essential oil of Cistus laurifolius L. from Turkey was analyzed by GC/MS. Sixty four compounds representing 67% of the oil were identified. Borneol (6.1%) and nonacosane (2.8%) were the major constituents.
Keywords: Cistus laurifolius; Cistaceae; essential oil composition